Ceremonia de Inauguración - Rivera Terrazas, Luis; Chávez Peón, Federico; Fernández de Lara, Alfredo Toxqui; Salmerón, Fernando; Bojalil, Luis Felipe; Quiroz Pérez, Miguel; Aguilar Hidalgo, José Manuel; Patiño Blanco, Raúl (Revista Mexicana de Ingenieria Biomedica, 2018)
Ceremonia de Inauguración